2013
DOI: 10.4236/as.2013.47050
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary assay on the mixed culture of red Florida tilapia and freshwater prawn <i>Macrobrachium americanum</i> stocked in outdoor tanks at different tilapia densities

Abstract: Red jumbo tilapia and M. americanum prawns were placed in 1000 L units in polyculture at three different densities of tilapia (4/5, 9/5 and 14/5 m 2 ; tilapia/prawn) during 112 days with initial weight of 6.5 ± 2.8 g for tilapia and 25.9 ± 8.5 g for prawn. Prawn (0/5 m 2) and tilapia (4/0, 9/0 and 14/0 m 2) controls were included. Tanks were maintained outdoors and under shade. Total weight gain (WG), daily individual weight gain (DWG), specific growth rate (SGR), survival, production of gross mass and food co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(56 reference statements)
1
4
1
Order By: Relevance
“…Most of the studies related to growth for caridian shrimp were performed with postlarvae and early juveniles under laboratory conditions (García-Guerrero and Apun-Molina 2008), adjusting an initial density of 98-196 individuals/m 2 (up to 2.7 g in weight). The mean weight obtained in this work after 120 d of culture (51.0 g) is higher than that obtained by Rojo-Cebreros et al (2013) for caridian shrimp (41.2 g) in clearwater plastic tanks, with an initial density of 5 individuals/m 2 at 25.3 g stocking size. The growth rate registered for the 5-g group (0.30 mm/d) is similar to that found by Arana-Magallón and Ortega-Salas (2005) for 2-g juveniles (0.36 mm/d) for the same prawn species cultured in laboratory conditions with clear water at 33 • C. However, the growth rate is higher than the growth rate of 0.1 mm/d found by Holtschmit (1988).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Most of the studies related to growth for caridian shrimp were performed with postlarvae and early juveniles under laboratory conditions (García-Guerrero and Apun-Molina 2008), adjusting an initial density of 98-196 individuals/m 2 (up to 2.7 g in weight). The mean weight obtained in this work after 120 d of culture (51.0 g) is higher than that obtained by Rojo-Cebreros et al (2013) for caridian shrimp (41.2 g) in clearwater plastic tanks, with an initial density of 5 individuals/m 2 at 25.3 g stocking size. The growth rate registered for the 5-g group (0.30 mm/d) is similar to that found by Arana-Magallón and Ortega-Salas (2005) for 2-g juveniles (0.36 mm/d) for the same prawn species cultured in laboratory conditions with clear water at 33 • C. However, the growth rate is higher than the growth rate of 0.1 mm/d found by Holtschmit (1988).…”
Section: Discussioncontrasting
confidence: 66%
“…For example, there are reports on larvae and postlarvae rearing under laboratory conditions (Monaco 1975;Holtschmit and Pfeiler 1984), its development and reproduction in controlled systems (García-Guerrero 2009;García-Guerrero 2010), the rearing of prawn juveniles under laboratory conditions (Arana-Magallón and Ortega-Salas 2005), and the adaptation of wild juveniles to culture conditions (Smitherman et al 1974;García-Guerrero and Apun-Molina 2008). Furthermore, the feasibility of polyculture has been tested with red tilapia (Mozambique Tilapia Oreochromis mossambicus × Wami Tilapia O. urolepis) in recirculating aquaculture systems (Rojo-Cebreros et al 2013). However, studies on the growth of juvenile M. americanum in earthen ponds and cage systems are scarce (Smitherman et al 1974;Arana-Magallón 1977).…”
mentioning
confidence: 99%
“…Performance of Chitralada and GIFT Survival rate of GIFT tilapia was significantly higher (P<0.05) (92.50%) than that of Chitralada (65.83%) might be due to less transportation stress which also helped to gain the highest gross and net production of tilapia. Cebreros et al (2013) observed, for tilapia, the highest survival was 94% and the lowest was 75%, while prawns had final survival rates from 43% to 86% (Table 3). The specific growth rate (SGR) of GIFT tilapia was significantly lower (P<0.05) in T 3 (4.52% of bw day ).…”
Section: Performance Of Prawnmentioning
confidence: 85%
“…Most recently, a study by Rojo-Cebreros et al (2013) found that M. americanum is a good companion for tilapia fish and does not interfere with fish production.…”
Section: Fisheries and Aquaculturementioning
confidence: 99%